Investing in Emergency Medicine to Improve Health Care for All Americans: The Role of the Agency for Healthcare Research and Quality - Mutter, Ryan; Clancy, Carolyn (Elsevier, 2013)
The Agency for Healthcare Research and Quality (AHRQ) is a component of the United States Department of Health and Human Services. AHRQ data show that there were nearly 129 million emergency department (ED) encounters in the United States in 2010, or approximately 1 ED visit for every 2.4 Americans.1 In addition, there were more than 17 million emergency medical services (EMS) responses in 2010.2 These high-frequency events profoundly affect the health and health care costs incurred by the people of the United States. Moreover, all of us depend on the ED being there when we or a loved one is in urgent need. Yet there are considerable gaps in the evidence base on the delivery of emergency medicine. The goal of this article is to show how AHRQ supports emergency medicine through the generation and dissemination of knowledge. As a vital component of its mission to improve the quality, safety, efficiency, and effectiveness of health care for all Americans, AHRQ supports research, the development of tools, the creation of quality indicators, the development of data and analytical capacity, and the training of young investigators.